2019
DOI: 10.3390/molecules24193581
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Brine Extraction for Enhancement of the Quantity and Quality of Lipid Production from Microalgae Nannochloropsis sp.

Abstract: Toward attaining a sustainability and eco-friendly process, a green and low-cost solvent—brine (NaCl solution) is proposed, as microwave-assisted extraction (MAE) technique solvent to extract lipids from microalgae Nannochloropsis sp. The effect of NaCl concentration on the quantity and quality of the extracted lipid was assessed, while MAE parameters were optimized using response surface methodology (RSM). The content of fatty acid methyl esters (FAMEs) in the lipid was analyzed by using a gas chromatography—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
(58 reference statements)
1
18
0
Order By: Relevance
“…The highest extraction temperature and longest extraction time of 100 • C and 30 min resulted in the highest lipid yield of 16.1%. According to previous work [6], this yield was three-fold better than that of Soxhlet extraction and only 2% less than achieved with the Bligh and Dyer (B&D) lipid extraction method, which utilizes harmful solvents. Table 1.…”
Section: Mae-brine Kinetics Modellingmentioning
confidence: 74%
See 3 more Smart Citations
“…The highest extraction temperature and longest extraction time of 100 • C and 30 min resulted in the highest lipid yield of 16.1%. According to previous work [6], this yield was three-fold better than that of Soxhlet extraction and only 2% less than achieved with the Bligh and Dyer (B&D) lipid extraction method, which utilizes harmful solvents. Table 1.…”
Section: Mae-brine Kinetics Modellingmentioning
confidence: 74%
“…The microwave extraction was performed in a 250 mL round bottom borosilicate flask. For the kinetic experiments, the optimised conditions from a previous work [6] were used with salt concentration of 10% (w/v) and solids loading of 5% (w/v). The runs were set for a maximum time of 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding the most efficient method and optimized conditions for the extraction of lipids were important for reducing the cost of biodiesel production from microalgae [10]. Based on literature studies, it was found the advantages and disadvantages of several existing extraction methods [12,13]. According to research that has been done by M. H. Kwon et al [13] in Table 2, BDM was mostly a solvent extraction process, which is influenced by factors such as the type of organic solvent, temperature, and cell wall rigidity.…”
Section: Extraction Process With the Soxhlet Methodsmentioning
confidence: 99%